Irańska polityka językowa: przypadek puryzmu językowego - Marszałek-Kowalewska, Katarzyna (Investigationes Linguisticae, 2010)
The aim of this article is to describe Iranian language policy from its officially recognized birth in the XVIII century up to today. It will focus on one particular aspect of language policy – linguistic purism. Firstly, the concept of vatan ‘Iranian nationalism’ will be defined. This article will try to explain the role of nationalism in Iranian language policy as well as its direct relations with purism. Then, the history of Iranian puristic movement will be addressed. It is divided into two separate periods on the basis of different elements that were considered unwanted. Therefore, the period before and after the Islamic Revolution of 1979 will be analyzed separately. Finally, certain conclusions will be drawn.